2010
DOI: 10.1111/j.1365-2265.2010.03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid axis dysfunction in patients with Prader‐Willi syndrome during the first 2 years of life

Abstract: The results of this study suggest that transient or definitive thyrotropin-releasing hormone (TRH)-TSH thyroid axis dysfunction may frequently be present in infant PWS patients. Paediatricians should be aware of this dysfunction in this critical period of thyroid hormone action on neurological development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Because hypothalamic neurocircuitry involved in energy homeostasis develops during the postnatal period (Bouret et al, 2004), we used ICR mice, which exhibit no lethality throughout the lifetime (Kuwako et al, 2005), and found that necdin deficiency caused dysfunction of the HPT axis during the juvenile period. Intriguingly, it has recently been reported that thyroid axis dysfunction is frequently present in PWS during the first two years of life (Vaiani et al, 2010). This clinical report suggests that hypothalamic hypothyroidism is a common feature in infants with PWS.…”
mentioning
confidence: 78%
“…Because hypothalamic neurocircuitry involved in energy homeostasis develops during the postnatal period (Bouret et al, 2004), we used ICR mice, which exhibit no lethality throughout the lifetime (Kuwako et al, 2005), and found that necdin deficiency caused dysfunction of the HPT axis during the juvenile period. Intriguingly, it has recently been reported that thyroid axis dysfunction is frequently present in PWS during the first two years of life (Vaiani et al, 2010). This clinical report suggests that hypothalamic hypothyroidism is a common feature in infants with PWS.…”
mentioning
confidence: 78%
“…Similar to other endocrinopathies in PWS, the etiology is thought to be central in origin. A recent study of children with PWS under 2 years of age revealed that 72.2% had abnormalities in the hypothalamic-pituitary-thyroid axis evidenced by low total or free thyroxine (FT4 ) in the presence of normal thyroid stimulating hormone (TSH) [82]. Studies of adult patients with PWS show that the frequency of thyroid disease is 2%, which is similar to that of the general population [83].…”
Section: Reviewmentioning
confidence: 97%
“…Expression of GHSR is positively regulated by thyroid hormone and estradiol, and negatively by cortisol (70). Indeed, hypothyroidism, hypogonadism, and elevated cortisol are all associated with PWS (71). Although not assessed quantitatively, GHSR1a expression appears normal in brains from deceased PWS patients (72).…”
Section: Implications Of Ghsr1:drd2 Heteromers In Obsessive Eating Asmentioning
confidence: 99%